Barclay, Katie, Sharon Crozier-De Rosa, y Peter N. Stearns, ed. Sources for the History of Emotions: A guide. Nueva York: Routledge, 2020, 251 p - Pinto Niño, Leonor Cecilia (Universidad Pedagógica y Tecnológica de Colombia, 2022)
Review Barclay, Katie, Sharon Crozier-De Rosa, y Peter N. Stearns, ed. Sources for the History of Emotions: A guide. NuevaYork: Routledge, 2020, 251 pp